PRINCIPLES OF MATERIAL SELECTION FOR TEACHING MOLECULAR PHYSICS USING INTERACTIVE TECHNIQUES - Aziza XAMIDOVA (Scholar Express Journal, 2024)
This article reflects the relevance of teaching molecular physics using interactive methods and the principles of selection of educational materials on the example of secondary schools. The article also shows the didactic properties and components of the principles of material selection in teaching molecular physics using interactive techniques.
Keywords: Teaching; molecular physics; interactive techniques